Performance Analysis of Object Placement Systems Based on Siemens S7-1200: Evaluation of Effectiveness and Accuracy: Performance Analysis of Object Placement Systems Based on Siemens S7-1200: Evaluation of Effectiveness and Accuracy - Siswoyo, Agus; Artanto, Dian (Universitas Putra Indonesia YPTK Padang, 2023)
The evolution of industrial automation systems has led to innovative solutions for efficient and precise object manipulation. This study introduces a groundbreaking